Facile synthesis of nitroamino-1, 3, 4-oxadiazole with azo linkage: a new family of high-performance and biosafe energetic materials. Issue 42 (19th October 2022) - Banik, Shreyasi; Kumar, Pradeep; Ghule, Vikas D.; Khanna, Shweta; Allimuthu, Dharmaraja; Dharavath, Srinivas
Abstract : Energetic materials serve as remarkable fuel/propellants for space shuttles, and their utility in civil and military applications is vast. Abstract : Energetic materials serve as remarkable fuel/propellants for space shuttles, and their utility in civil and military applications is vast. The emergence of new and powerful energetic materials possessing signature chemical structures such as nitroaromatics and oxygen/nitrogen-rich heterocyclic scaffolds continues to evolve. Nitrogen-rich materials add to the advantage of being "green" energetic materials by eliminating oxidative carbon dioxide released into the atmosphere. Here, we report for the first time a single-step synthesis of nitrogen-rich (5, 5′-dinitramino-3, 3′-azo-1, 3, 4-oxadiazole (5 ) and its energetic salts obtained in quantitative yields from commercially available inexpensive starting materials. Our set of molecules possessed superior energetic properties to those of benchmark explosives HMX, ε-CL-20, and ICM-101. Among these, compound 5 exhibited an exceptional energetic property with a remarkable density of 1.97 g cm −3 at 298 K, high positive heat of formation (405.7 kJ mol −1 ), high detonation velocity, pressure (9358 m s −1 and 39.1 GPa), good thermal stability (185 °C), and acceptable impact and friction sensitivity (6 J and 160 N). Compound 5 was recognized as a potential less sensitive HEDM with a planar and high symmetry crystal structure. Our effort to assess the toxicity profiles of our compounds against human embryonic kidney cells indicated the compounds are biosafe and nontoxic even at the concentration of 50 μM. Together, our study points to an incredible green, high energetic material with signs of evolving to give next-generation secondary energetic materials in space, civil and military applications.